Design of Alkali Pozzolan Cement (APC): Early Compressive Strength - Kulasuriya, Chandana; Vimonsatit, Vanissorn; Dias, W. P. S. (Research Publishing Services, 2012)
This paper explores the feasibility of producing Alkali Pozzolan Cement (APC), a cementitious mixture obtained by mixing alkali materials and pozzolanic materials along with some other chemicals. Pozzolanic material used in the experiments is fly ash and the alkali-generating material used is quicklime. The two critical issues related to fly ash-quicklime mixture are slow reaction and slow hardening process. These issues were resolved by adding ‘activating chemicals’ and ‘scaffolding chemicals’. It is seen that early strength of APC can be significantly improved by adding activating and scaffolding chemicals. Finally the paper proposes a development of a multi-dimensional matrix, by varying the percentages of constituent materials, to determine the optimum APC mixture.